Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Pictet-Spengler cyclization in room temperature ionic liquid: a convenient access to tetrahydro beta-carbolines - Muthukrishnan, Murugan; More, Shivaji V.; Garud, Dinesh R.; Ramana, C. V.; Joshi, Rohini R.; Joshi, Ramesh A. (Journal of Heterocyclic Chemistry, 2006)
1,2,3,4-Tetrahydro-beta-carbolines have been synthesized in moderate to good yields in short reaction time using the ionic liquid [bbim] BF4 as reaction medium and promoter. There was no need for the use of an additional catalyst normally employed in Pictet-Spengler condensation.

Pd(II)-mediated alkynediol spiroketalization: first total synthesis of (-)-cephalosporolide E and (+)-cephalosporolide F - Ramana, C. V.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2009)
Herein we describe a concise assembly of the central 1.6-dioxaspiro[4.4]nonane core of cephalosporolides E/F by employing a Pd-mediated alkynediol cycloisomerization and their total synthesis. On the basis of spectroscopic data and optical rotation values, the absolute configurations of cephalosporolides E/F were proposed.

Pd-mediated intramolecular ketalization of alkynediols: construction of the central [3.2.1]-bicyclic ketal core of cyclodidemniserinol trisulfate - Ramana, C. V.; Mallik, Rosy; Sahoo, Gokarneswar (Tetrahedron Letters, 2009)
A preliminary study dealing with the Pd-mediated alkynediol cycloisomerization to construct the central bicyclic ketal core of cyclodidemniserinol trisulfate is documented. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Cyclodidemniserinol trisulfate; Yamaguchi oxirane-alkyne coupling

Polarization switching characteristics of 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) lead free ferroelectric thin films by pulsed laser deposition - Kolekar, Y. D.; Bhaumik, A.; Shaikh, P. A.; Ramana, C. V.; Ghosh, K. (JOURNAL OF APPLIED PHYSICS, 2014)
We report on the ferroelectricity for morphotropic-phase-boundary lead (Pb) free 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) (0.5BZT-0.5BCT) thin films. Thin films were grown on Pt/Ti/SiO2/Si substrate using pulsed laser deposition. Raman spectroscopic data combined with the X-ray diffraction analyses confirm body centered tetragonal crystallographic structure 0.5BZT-0.5 BCT thin films on Pt/Ti/SiO2/Si. Polarization studies demonstrate that these 0.5BZT-0.5BCT films exhibit a large remnant and saturation polarization of 37 mu C/cm(2) and 40 mu C/cm(2), respectively, with a coercive field of 140 kV/cm. A correlation between polarization dynamics, structural distortion, and phonon vibration is established. The splitting of X-ray diffraction peak of the thin film in the 2 theta range of 44.5 degrees to 46.5 degrees represents high degree of tetragonality. The tetragonality factor calculated by Rietveld analysis was found to be 0.006 and can be a major cause for the increased remnant polarization value. It is established from Raman spectra that the non-centrosymmetricity due to the displacement of Ti/Zr ions from its octahedral position is related to the peak position as well as the broadening of the A(1) (LO) optical phonon mode. This increase of broadness in the thin film causes an increase in the dipole moment of the unit cell and, hence, the net increase in polarization values. (C) 2014 AIP Publishing LLC.

Pd-catalyzed benzylic C-H oxidation of cyclotriveratrylene - product diversity - Senthilkumar, B.; Gonnade, Rajesh G.; Ramana, C. V. (Organic & Biomolecular Chemistry, 2015)
The inner-rim functionalization of CTV has been examined by employing Pd-catalyzed benzylic oxidation. The outcome of the oxidation depends upon the solvent and co-oxidants employed. An interesting array of CTV derivatives has been synthesized with a simple change in the conditions.